2010
DOI: 10.1016/j.gaceta.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y validación de un cuestionario para medir la continuidad asistencial entre niveles desde la perspectiva del usuario: CCAENA

Abstract: The questionnaire (CCAENA) seems to be an useful, valid and reliable instrument to assess comprehensively continuity between levels of care from the user's perspective. Further information about the questionnaire's psychometric properties will be obtained by applying it to a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
7
0
6
Order By: Relevance
“…Most available instruments are addressed to specific populations [8], such as patients with diabetes [9,10], cancer [11,12], mental illness [13,14] and patients with an unspecified chronic disease [15] or aimed at users attended to in primary care settings or as inpatients [16,17]. The first generic tool developed to address continuity of care across care levels as perceived by health care users, regardless of morbidity, was the CCAENA© questionnaire (Cuestionario Continuidad Asistencial Entre Niveles de AtenciÓn)[18]. This tool is divided into two sections: the first reconstructs the care trajectory for a specific episode, and the second, which is the object of this paper, consists of Likert scales that measure the patients’ perceptions of the three types of continuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most available instruments are addressed to specific populations [8], such as patients with diabetes [9,10], cancer [11,12], mental illness [13,14] and patients with an unspecified chronic disease [15] or aimed at users attended to in primary care settings or as inpatients [16,17]. The first generic tool developed to address continuity of care across care levels as perceived by health care users, regardless of morbidity, was the CCAENA© questionnaire (Cuestionario Continuidad Asistencial Entre Niveles de AtenciÓn)[18]. This tool is divided into two sections: the first reconstructs the care trajectory for a specific episode, and the second, which is the object of this paper, consists of Likert scales that measure the patients’ perceptions of the three types of continuity.…”
Section: Introductionmentioning
confidence: 99%
“…The initial validation of the CCAENA questionnaire indicated that this is a useful instrument to assess continuity of care from the patients’ point of view [18]: face and content validity were high, comprehensibility was considered adequate and the interviewer burden was acceptable [18]. Moreover, items showed an adequate internal structure (construct validity), and scales reached acceptable levels of internal consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Para la APS es de suma importancia contar con sistemas de información que permitan hacer seguimiento respecto de lo que ocurre con la población a cargo 8,24 para asegurar el acceso a una atención de salud oportuna y continua que se ha demostrado impacta directamente en la disminución del gasto en salud y la mejora de la atención preventiva 25,26 . En síntesis, los resultados del estudio pueden servir para orientar la gestión clínica y administrativa y la praxis habitual en la atención de los equipos de salud en prácticas que permitan el fortalecimiento de la instalación del MAIS en APS de acuerdo a sus principios orientadores y a las distintas realidades locales, los que se vinculan a mejores índices de satisfacción usuaria y de resultados clínicos a mediano y largo plazo como también en la organización y coordinación de los servicios que proveen los prestadores de salud, lo que impacta en la calidad de la atención y la disminución de los costos globales de atención 4,15,27 .…”
Section: Discussionunclassified
“…En este número de Revista Española de Salud Pública Aller y colaboradores 9 abordan en el escenario asistencial real y diario la evaluación cuantitativa por parte de los usuarios de los factores que se relacionan con la continuidad asistencial, y los distintos grados alcanzados en las dimensiones referidas de ésta, validando paralelamente el cuestionario utilizado 10 .…”
Section: Editorialunclassified